The Effects of the Health Insurance Card Scheme on Out-of-Pocket Expenditure Among Migrants in Ranong Province, Thailand - Suphanchaimat R; Kunpeuk W; Phaiyarom M; Nipaporn S (Dove Medical Press, 2019)
Rapeepong Suphanchaimat,1,2 Watinee Kunpeuk,1 Mathudara Phaiyarom,1 Sirinard Nipaporn3 1International Health Policy Program, Ministry of Public Health, Nonthaburi 11000, Thailand; 2Division of Epidemiology, Department of Disease Control, Ministry of Public Health, Nonthaburi 11000, Thailand; 3National Health Security Office, Bangkok 10210, ThailandCorrespondence: Rapeepong Suphanchaimat Tel +66-2-590-2366Fax +66-2-590-2385Email rapeepong@ihpp.thaigov.netIntroduction: Although Thailand achieved Universal Health Coverage since 2002, there remained gaps in the insurance coverage as undocumented migrants were ineligible to be enrolled in the national public insurance. In 2004 the Thai Ministry of Public Health implemented the Health Insurance Card Scheme (HICS) to cover undocumented migrants. The objective of this study was to investigate the effect of the HICS on out-of-pocket payments (OOP) made by migrant patients at point of care.Methods: The study applied quantitative methods, using individual patient records from one provincial hospital, one district hospital and two health centers between 2011 and 2015. Ranong province was chosen as a study site as it had the largest proportion of migrants to Thai residents compared with other provinces. Descriptive and inferential statistics were employed. In descriptive statistics, mean and median were used. In inferential statistics, the two-part model (TPM) was applied to examine the relationship between the HICS and OOP for both outpatient (OP) and inpatient (IP) care.Results: The HICS reduced IP and OP OOP expenditures by 2471 Baht (US$ 75) and 293 Baht (US$ 9) respectively. The attributes contributed to the reduction of IP and OP OOP included insurance status, residential address close to the facilities, and a history of visiting health facilities after 2013 (the year that the HICS expanded its benefit package). In contrast, severe illness, and advanced age were expected to increase IP and OP OOP.Conclusion: The HICS appeared to reduce the financial burden from accessing care among its beneficiaries. Future studies to explore supply-side financing and equity aspects of the impact of HICS on OOP are recommended.Keywords: migrants, out-of-pocket expenditure, two-part model, health insurance